PERLINDUNGAN HUKUM TERHADAP USAHA MIKRO. KECIL DAN MENENGAH DALAM PASAR BEBAS ASEAN-CHINA FREE TRADE AREA - YUNITA PANJAITAN; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
ACFTA (ASEN-China Free Trade Agreement) is a regional free trade agreement among the states member of ASEAN and China. One of the advantage of ACFTA is to increase the export of Indonesia product to the international market. So, the products from Indonesia such as the product of Micro, Small and Medium Scale busines can be developed. The weakness position of UMKM in the bigger industry products, to ake UMKM still in a weak position by the presence of China products through this ACFTA agreement. This condition cause any problems. Therefore, in order to avoid any problems faced by UMKM, the government determine three competitive protection, i.e. antidumping, the protection through Safeguard and determine the duty to the Chine product that do any violation in the impolementation of ACFTA agreement. Keywords : UMKM, ACFTA